Role of Mask in Prevention of Infection - A Review - NAVEENAA, N.; ARIVARASU, LAKSHMINARAYANAN; RANI, LESLIE (The journal of contemporary issues in business and government, 2020)
The personal protective equipment is used in the prevention of infection during pandemic. Non pharmaceutical intervention intervention is like masks play a major role in the prevention of community spread of infection. There are different types of March which have different functions and should be indicated only for certain people, not any person can wear any type of mask.The role of face mask has played a major role in controlling and prevention of spread of disease through aerosol contamination in COVID- 19. It is a key control, which drops down the respiratory infection of virus spread and not only for COVID-19,it was highly used for tuberculosis, influence patients and the doctors who treat them.Appropriate choosing and using it and a disposal mask is very important as wearing a mask to prevent infection.This review emphasises the need, use of appropriate mask in infection control.With the possible literature masks are used as a key in prevention of infection at community level but there is an acute demand which arises due to improper use so it is essential in choosing a proper mask so that the resources are available for the entire population.